(3GdUfGYGJ GdUZjQI hOhQgG aj GdJfejI GdEbJUGOjI hGdSjGMjI (B/s - (3EHQGgje, fgi EHQGgje Ndjds ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2009)
(3jVe GdChVGY GdEbJUGOjI hGdKbGajI ddUfGYGJ GdMQajI, CgejI GdefJLGJ GdMQajI GdJPcGQjI aj UfGYI GdSjGMI eY GdETGQI GdNGUI deUQ, GdeTcdGJ GdEfJGLjI hGdJShjbjI ddefJLGJ GdMQajI GdJPcGQjIs
(3GdeQGLY U(B.227s
Keywords: (3GdJfejI GdEbJUGOjIs; (3GdMQa GdjOhjI(B- (3eUQs; (3GdSjGMIs; (3GdUfGYGJ GdjOhjIs